Harnessing immunotherapeutic molecules and diagnostic biomarkers as human-derived adjuvants for MERS-CoV vaccine development - Alrasheed, Abdullah R.; Awadalla, Maaweya; Alnajran, Hadeel; Alammash, Mohammed H.; Almaqati, Adil M.; Qadri, Ishtiaq; Alosaimi, Bandar (Frontiers in Immunology, 2025)
The pandemic potential of the Middle East Respiratory Syndrome Coronavirus (MERS-CoV) highlights the critical need for effective vaccines due to its high fatality rate of around 36%. In this review, we identified a variety of immunotherapeutic molecules and diagnostic biomarkers that could be used in MERS vaccine development as human-derived adjuvants. We identified immune molecules that have been incorporated into standard clinical diagnostics such as CXCL10/IP10, CXCL8/IL-8, CCL5/RANTES, IL-6, and the complement proteins Ca3 and Ca5. Utilization of different human monoclonal antibodies in the treatment of MERS-CoV patients demonstrates promising outcomes in combatting MERS-CoV infections in vivo, such as hMS-1, 4C2H, 3B11-N, NBMS10-FC, HR2P-M2, SAB-301, M336, LCA60, REGN3051, REGN3048, MCA1, MERs-4, MERs-27, MERs-gd27, and MERs-gd33. Host-derived adjuvants such as CCL28, CCL27, RANTES, TCA3, and GM-CSF have shown significant improvements in immune responses, underscoring their potential to bolster both systemic and mucosal immunity. In conclusion, we believe that host-derived adjuvants like HBD-2, CD40L, and LL-37 offer significant advantages over synthetic options in vaccine development, underscoring the need for clinical trials to validate their efficacy.